2000
DOI: 10.1093/ajcn/71.2.472
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering effects of psyllium intake adjunctive to diet therapy in men and women with hypercholesterolemia: meta-analysis of 8 controlled trials

Abstract: Psyllium supplementation significantly lowered serum total and LDL-cholesterol concentrations in subjects consuming a low-fat diet. Psyllium is well tolerated and safe when used adjunctive to a low-fat diet in individuals with mild-to-moderate hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
1
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(145 citation statements)
references
References 29 publications
6
134
1
4
Order By: Relevance
“…In this study, HDL-cholesterol concentration increased significantly by 0.07 mmol/l in both PDX and SBP groups, however, without a significant difference as compared with the control group. Previous studies have shown a small decrease by soluble fiber in serum total and LDL-cholesterol concentrations without a decreasing effect on HDL-cholesterol (Brown et al, 1999;Knopp et al, 1999;Anderson et al, 2000;Vuksan et al, 2000). Regarding concentrations of serum triglycerides, the results are controversial; in some studies dietary fiber has been shown to have no effect on the concentration of serum triglycerides (Vuksan et al, 1999(Vuksan et al, , 2000, whereas in some other studies a decreasing effect of dietary fiber has been reported (Chandalia et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, HDL-cholesterol concentration increased significantly by 0.07 mmol/l in both PDX and SBP groups, however, without a significant difference as compared with the control group. Previous studies have shown a small decrease by soluble fiber in serum total and LDL-cholesterol concentrations without a decreasing effect on HDL-cholesterol (Brown et al, 1999;Knopp et al, 1999;Anderson et al, 2000;Vuksan et al, 2000). Regarding concentrations of serum triglycerides, the results are controversial; in some studies dietary fiber has been shown to have no effect on the concentration of serum triglycerides (Vuksan et al, 1999(Vuksan et al, , 2000, whereas in some other studies a decreasing effect of dietary fiber has been reported (Chandalia et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is strongly supported by evidence from dietary interventions that have demonstrated the ability of ancestral food components such as viscous fibres, plant sterols, vegetable proteins and nuts to reduce the risk of heart disease by lowering serum cholesterol levels (21)(22)(23)(24)(25) . The strength of the evidence has prompted various bodies such as the American Heart Association (26) , the Adult Treatment Panel III of the National Cholesterol Education Program (NCEP) (7) and the US Food and Drug Administration (27)(28)(29)(30)(31) to endorse the intake of these food components.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 87%
“…Soluble fibre appears to be primarily responsible for the cholesterol-lowering effect of dietary fibre intake (57) . Studies in HC patients without treatment with cardiovascular drugs showed that addition of soluble fibres (psyllium (58,59) , b-glucan (60 -63) , guar gum (64,65) , pectin (66) ) to a low-fat, lowcholesterol diet was an effective approach to reduce total and LDL-cholesterol. The mechanisms involved are not completely understood, but it is suggested that soluble fibres reduce plasma cholesterol by interruption with cholesterol and/or bile acid (re)absorption (67) .…”
Section: Mechanism Of Supporting Statin Therapymentioning
confidence: 99%
“…Also the time of drug administration in relation to food intake may influence the bioavailability of the drug. Soluble fibres may influence the bioavailability of statins and other drugs by direct binding or by altering luminal pH, gastric emptying, intestinal transit, mucosal absorption and metabolism of the drug (58,82) .…”
Section: Safety Aspects Of Combination Therapy With Soluble Dietary Fmentioning
confidence: 99%